(untitled) (Washington, D.C., 2008)
Contents: the development of education in Singgapore since 1965; strategic management of educational development.
Keywords: Vocational education,Singapore,Giáo dục dạy nghề,Điều kiện kinh tế; Economic conditions; Singapore,Singapore,Singapore